RAILWAY SECURITY SYSTEM WITH HALL EFFECT SENSOR BASED ON ARDUINO UNO - Syamsu Marlin; Prawiro Harjono; Ahmad Refo Syatomy (Jurnal Scientia, 2022)
This railway door security system is made and can be used to overcome problems that exist in railroad crossing doors. The large number of cases and fatalities that have occurred to date have been caused by a lack of security and the large number of individuals who have committed acts of violations, causing many fatalities and other cases that have occurred at railroad crossings. The existence of these tools and systems can change mindsets and reduce the number of accidents at railroad crossings. Because the system in this prototype is able to provide a deterrent effect to persons who violate the rules. Overall this tool can work and function properly according to the desired system. The sensor output voltage is around 3 – 5V DC. Hopefully this tool can be a reference for improving the existing system at the current train gate. So that the number of accidents that occur at railroad crossings can be reduced.